Modeling Major Adverse Outcomes of Pediatric and Adult Patients With Congenital Heart Disease Undergoing Cardiac Catheterization: Observations From the NCDR IMPACT Registry (National Cardiovascular Data Registry Improving Pediatric and Adult Congenital Treatment). Issue 21 (21st November 2017) - Jayaram, Natalie; Spertus, John A.; Kennedy, Kevin F.; Vincent, Robert; Martin, Gerard R.; Curtis, Jeptha P.; Nykanen, David; Moore, Phillip M.; Bergersen, Lisa
Abstract : Background: Risk standardization for adverse events after congenital cardiac catheterization is needed to equitably compare patient outcomes among different hospitals as a foundation for quality improvement. The goal of this project was to develop a risk-standardization methodology to adjust for patient characteristics when comparing major adverse outcomes in the NCDR's (National Cardiovascular Data Registry) IMPACT Registry (Improving Pediatric and Adult Congenital Treatment). Methods: Between January 2011 and March 2014, 39 725 consecutive patients within IMPACT undergoing cardiac catheterization were identified. Given the heterogeneity of interventional procedures for congenital heart disease, new procedure-type risk categories were derived with empirical data and expert opinion, as were markers of hemodynamic vulnerability. A multivariable hierarchical logistic regression model to identify patient and procedural characteristics predictive of a major adverse event or death after cardiac catheterization was derived in 70% of the cohort and validated in the remaining 30%. Results: The rate of major adverse event or death was 7.1% and 7.2% in the derivation and validation cohorts, respectively. Six procedure-type risk categories and 6 independent indicators of hemodynamic vulnerability were identified. The final risk adjustment model included procedure-type risk category, number of hemodynamic vulnerability indicators, renal insufficiency, single-ventricle physiology, and coagulation disorder. The model had good discrimination, with a C-statistic of 0.76 and 0.75 in the derivation and validation cohorts, respectively. Model calibration in the validation cohort was excellent, with a slope of 0.97 (standard error, 0.04; P value [for difference from 1] =0.53) and an intercept of 0.007 (standard error, 0.12; P value [for difference from 0] =0.95). Conclusions: The creation of a validated risk-standardization model for adverse outcomes after congenital cardiac catheterization can support reporting of risk-adjusted outcomes in the IMPACT Registry as a foundation for quality improvement. Abstract : Supplemental Digital Content is available in the text.